Elastic collision and breather formation of spatiotemporal vortex light bullets in a cubic-quintic nonlinear medium - Adhikari, S. K. [UNESP] (IOP Publishing, 2017)
The statics and dynamics of a stable, mobile three-dimensional (3D) spatiotemporal vortex light bullet in a cubic-quintic nonlinear medium with a focusing cubic nonlinearity above a critical value and any defocusing quintic nonlinearity are considered. The present study is based on an analytic variational approximation and a full numerical solution of the 3D nonlinear Schrödinger equation. The 3D vortex bullet can propagate with constant velocity. Stability of the vortex bullet is established numerically and variationally. Collision between two vortex bullets moving along the angular momentum axis is considered. At large velocities the collision is quasi-elastic, with the bullets emerging after collision with practically no distortion. At small velocities two bullets coalesce to form a single entity called a breather.
Keywords: NLS equation; soliton; vortex bullet